Applying the One Health Framework to Historical Mining Activities: Interconnected Ecosystem and Community Health Impacts of Acid Mine Drainage in the Witwatersrand - Grama, Vasile; Ecer, Zeynep Ceylin; Curtis, Chris (Mdpi, 2026)
Gold mining in South Africa's Witwatersrand Basin represents a critical case study of mining-induced environmental degradation affecting interconnected ecological and human systems. While the cascading effects of acid mine drainage (AMD), originating from a legacy of approximately 270 tailings dams containing 6 billion tons of FeS2 waste and 600,000 tons of residual uranium, are widely documented, this evidence often remains fragmented. This study applies a systematic, framework-based analytical approach that integrates multidisciplinary evidence from geochemical, ecological, agricultural, and public health research within a One Health/EcoHealth perspective. Qualitative field observations are used to contextualize and validate the analytical synthesis along the water-soil-food-human continuum. A four-pathway conceptual model, including environmental dispersion, biotic uptake, trophic transfer, and direct human exposure, is developed to structure and interpret the integrated findings. The results demonstrate that mining-derived contaminants propagate through interconnected pathways, leading to persistent contamination of water resources, agricultural systems, and human communities, particularly within the Wonderfonteinspruit watershed. Evidence synthesized across pathways reveals extreme bioaccumulation and exposure levels and elevated uranium levels in the hair of local children. The study concludes that the impacts of acid mine drainage constitute a systemic socio-ecological failure driven by cumulative and interacting exposure pathways that cannot be effectively addressed through sectoral or single-medium interventions. The principal contribution of this research is the development of an operational, transferable framework that enables integrated risk assessment and supports evidence-based management and remediation strategies in post-mining landscapes.
Keywords: acid mine drainage; Witwatersrand basin; one health/ecohealth approach; gold mining impacts; heavy metal contamination